2014
DOI: 10.1002/jmrs.56
|View full text |Cite
|
Sign up to set email alerts
|

A paediatric X‐ray exposure chart

Abstract: The aim of this review was to develop a radiographic optimisation strategy to make use of digital radiography (DR) and needle phosphor computerised radiography (CR) detectors, in order to lower radiation dose and improve image quality for paediatrics. This review was based on evidence-based practice, of which a component was a review of the relevant literature. The resulting exposure chart was developed with two distinct groups of exposure optimisation strategies – body exposures (for head, trunk, humerus, fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Many studies still advocate the use of a low kV and relatively high mAs values as standard practice, 3,9,21 although Rizzi et al 9 did conclude after an optimisation study that higher kV and lower mAs can reduce the radiation dose and still provide the same image quality (60 kV/1 mAs). Another attempt was made 22 to systematically search the literature for paediatric radiography exposure techniques and subsequently develop an updated paediatric exposure chart. This study concluded that the optimal exposure factors for a neonate (0e6 months) were 63 kVp and 1.6 mAs which is still much higher than the average exposure factors found within the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies still advocate the use of a low kV and relatively high mAs values as standard practice, 3,9,21 although Rizzi et al 9 did conclude after an optimisation study that higher kV and lower mAs can reduce the radiation dose and still provide the same image quality (60 kV/1 mAs). Another attempt was made 22 to systematically search the literature for paediatric radiography exposure techniques and subsequently develop an updated paediatric exposure chart. This study concluded that the optimal exposure factors for a neonate (0e6 months) were 63 kVp and 1.6 mAs which is still much higher than the average exposure factors found within the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This was reinforced by some exposure charts having only one recommended kV and mAs for neonates aged 0e6 months. 22 Seven (37%) of the responding departments used a set SID for acquiring CXRs on neonates within the incubator, however only three specified this distance (100 cm). Over half of the remaining responding departments used the maximum achievable SID for imaging the neonatal chest within incubators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray tube current was set at 100 milliamperes (mA) and the time of exposure was 0.02 sec (s)(2 mAs) (Knight, 2014). Plastic wedges were mounted on the collimator of X-ray machines.…”
Section: Methodsmentioning
confidence: 99%
“…PMMA was used as the soft tissue equivalent [24,25] (Figure 1). PoP has been reported [25] as a possible cortical bone substitute and has been used in literature for imaging of paediatric distal extremities [26] and the construction of body contours [27]. The problem with this substitute is that its density does not exactly match that of paediatric cortical bone [28].…”
Section: 11-materials Selectionmentioning
confidence: 99%